Chapter 19 Max Ritvo's Precision Poetry - Choksey, Lara (Springer Nature, 2020)
This essay reads Max Ritvo's poetry through a chronology of precision biomedicine: imaging, diagnosis, and treatment. Ritvo's construction of a patient-consumer avatar in his poetry reflects his position at a biomedical frontier, while poetic form becomes a way of retrieving bodies from a logic of substitution and surrogacy.